An Experimental Approach to Buddhism and Religion - Nelson, John K. (International journal of Dharma Studies, 2017)
Adaptations, modifications, and realignments of religious doctrine and practice can be found in any period of social history. It can be official and highly orchestrated (as in Vatican II) but more often it takes a subjective and reactionary form (as in the Hindutva movement). This paper promotes the idea of "experimental religion" as both an analytical concept and an observable set of behaviors that help identify how contemporary trends (such as individualism, secularity, information technologies, and market economies) reconfigure attitudes and motivations regarding the relevance and applicability of religious resources. Drawing from Buddhist-related case material in Japan and other liberal democracies, we see lay practitioners, priests, and occasionally institutions as well using innovation and activism to reposition and reboot existing paradigms. The intention is to fashion a religious practice responsive to individual concerns as well as to pressing environmental, political, and economic issues.